Analysis of the combinative effect of ultrasound and microwave power on Saccharomyces cerevisiae in orange juice processing. (December 2015) - Samani, Bahram Hosseinzadeh; Khoshtaghaza, Mohammad Hadi; Lorigooini, Zahra; Minaei, Saeid; Zareiforoush, Hemad
Abstract: High temperature in conventional method for juice pasteurization causes adverse effects on nutrients and nutritional value of food. The objective of this study was to examine the effect of microwave output power, temperature, ultrasound power, and ultrasonic exposure time on Saccharomyces cerevisiae in orange juice. Based on our findings, microwave output power, ultrasound power, ultrasonic exposure time orange juice temperature were the most effective factors to reduce S. cerevisiae . The results showed that the quadratic model included was the best model for account. The model showed that regarding decrease of S. cerevisiae account microwave-induced temperature was more effective than microwave output power. Also, compared to microwave power, the ultrasound power was more effective on S. cerevisiae reduction. The optimum processing condition was 350 W microwave power, 35 °C temperature, 778.2 W ultrasonic power, and 11 min of exposure. Based on our result, the consumption energy was 142.77 J/mL with no remaining of S. cerevisiae . The results showed that the given scores by panelists to the combinative and conventional methods for color and flavor indices were significant ( P  < 0.05). Industrial Relevance: In order to reduce the adverse effects (loss of vitamins, flavor, and non-enzymatic browning) of the thermal pasteurization method, other methods capable of inactivation of microorganisms can be applied. In doing so, non-thermal methods are of interest, including pasteurization using high hydrostatic pressure processing (HPP), electric fields, and ultrasound waves. The ultrasound technology has been the main focus of studies in recent years. However, the main challenge facing the non-thermal technologies in food processing is the inactivation of pathogenic microorganisms and food spoilage agents, which can be achieved by various methods. The aim of present research was examined simultaneous effect of ultrasonic and microwave to remove microorganism. This research introduces new, innovative, and combined method for fruit juice pasteurization, and this method can benefit the food industry. Highlights: Microwave output power, ultrasound power, and ultrasonic exposure time orange juice temperature were the most effective factors to reduce S. cerevisiae . The importance of final temperature of orange juice effect on reducing S. cerevisiae is considered higher than the importance of microwave power which leads to the temperature. Compared to microwave power, the ultrasound power was more effective on S. cerevisiae reduction. Sample temperature and duration of ultrasonic treatment are taken into account as important and effective independent variables in relation to reducing S. cerevisiae .